Associations between socioeconomic position and young people's physical activity and sedentary behaviour in the UK: a scoping review. Issue 5 (2nd May 2022) - Pearson, Natalie; Griffiths, Paula; van Sluijs, Esther; Atkin, Andrew J; Khunti, Kamlesh; Sherar, Lauren B
Abstract : Objective: To examine the evidence on the associations between socioeconomic position and young people's physical activity and sedentary behaviours in the UK. Design: Scoping review. Data sources: PubMed, SCOPUS and Web of Science databases were searched for articles published up to and including January 2021. Eligibility criteria for selecting studies: Observational studies in children and adolescents (aged 5–18 years) from the UK that had assessed associations between at least one indicator of socioeconomic position and at least one outcome of physical activity and/or sedentary behaviour. Data extraction and synthesis: Data were extracted by one reviewer and 20% were double checked. Indicators of socioeconomic position were tabulated with domains of physical activity and sedentary behaviour. Results: Fifty-seven publications were included in the review; 37 publications from 19 studies (k=23) of children and 21 publications from 15 studies (k=23) of adolescents. Most studies were cross-sectional. 63% of studies of children, and 40% of studies of adolescents assessed Index of Multiple Deprivation. Eighteen studies measured physical activity in children, 13 measured sedentary behaviour. Eleven studies of adolescents included a measure of physical activity, 10 included a measure of sedentary behaviour. Among children and adolescents, the association between socioeconomic position and measures of either physical activity or sedentary behaviour was highly variable depending on the measure of both socioeconomic position used and the behavioural outcome, with the exception of higher family affluence which was consistently associated with higher reported physical activity among adolescents. Conclusion: Physical activity and sedentary behaviours of children and adolescents in the UK are complex and influenced by multiple indicators of socioeconomic position that are, in most cases, different across age stages, outcomes examined and measurement tools. Greater consistency in the use and measures of socioeconomic position as well as outcomes of behaviour are required for robust country-specific meta-analyses.